2019
DOI: 10.1080/15384101.2019.1593648
|View full text |Cite
|
Sign up to set email alerts
|

microRNA 92b-3p regulates primordial follicle assembly by targeting TSC1 in neonatal mouse ovaries

Abstract: The primordial follicle pool, providing all oocytes available to a female throughout her reproductive life, is established perinatally. The formation of primordial follicle pool is regulated by precise transcriptional and post-transcriptional mechanisms. Recent studies have identified several microRNAs as post-transcriptional regulatory factors in the process of primordial follicle assembly.Here, we showed that miR-92b-3p was significantly upregulated in the stage of primordial follicle assembly in newborn mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…For instance, miR‐92b‐3p down‐regulation prevents lung cancer cell growth via targeting reversion‐inducing‐cysteine‐rich protein with kazal motifs (RECK; Lei, Huang, & Gong, 2014). MiR‐92b‐3p targets tuberous sclerosis complex 1 (TSC1) to regulate primordial follicle assembly in neonatal mouse ovaries (Li et al., 2019). Phosphatase and tensin homologue (PTEN) and Smad7 are direct targets of miR‐92b‐3p in various cells (Li, Li et al., 2013; Song et al., 2016b; Wang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR‐92b‐3p down‐regulation prevents lung cancer cell growth via targeting reversion‐inducing‐cysteine‐rich protein with kazal motifs (RECK; Lei, Huang, & Gong, 2014). MiR‐92b‐3p targets tuberous sclerosis complex 1 (TSC1) to regulate primordial follicle assembly in neonatal mouse ovaries (Li et al., 2019). Phosphatase and tensin homologue (PTEN) and Smad7 are direct targets of miR‐92b‐3p in various cells (Li, Li et al., 2013; Song et al., 2016b; Wang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that nuclear lncRNA regulates miRNA expression by suppressing its maturation process in the nucleus 33 , 34 . Given that Xist is also a nuclear lncRNA and that miRNAs are essential to promote oocyte survival and decrease apoptosis 26 29 , we wondered whether Xist may also play such a role in regulating oocyte death during PF formation. Previous studies have profiled differentially expressed miRNAs for association with premature ovarian failure development in both animal models and patients, including miR-23b-3p and miR-29a-3p 35 , 36 .…”
Section: Resultsmentioning
confidence: 99%
“…The mature miRNA is finally generated once one strand is discarded. It is well acknowledged that miRNAs can negatively control the expression of target genes in a wide range of cell signaling pathways related to different physiological and pathological processes 24 , 25 , including PF formation and even POI 26 29 . However, these studies focus more on how these miRNAs regulate their downstream targets and participate in the regulation of PF formation, and reports of miRNA biogenesis and regulation are missing.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is cardiac hypertrophy, which is suppressed in mice by miR-92b-3p, potentially by targeting MEF2D [ 250 ] and HAND2 [ 251 ]. Furthermore, it can inhibit the pulmonary artery derived smooth muscle cells proliferation by targeting USP28 [ 281 ], as well as regulate the assembly of primordial follicles in the ovaries of neonatal mice by targeting TSC1 [ 282 ]. In cancer, miR-92b-3p have both anti- and pro-cancer roles in different types of cancers: it suppresses pancreatic cancer by targeting GABRA3 [ 252 ], but promotes several others such as colorectal cancer by inhibiting FBXW7 [ 253 ], esophageal squamous cell carcinoma by target KLF4 and DCS2 [ 254 ], gastric cancer by downregulating MMP2, MMP9 and HOXD10 [ 255 ], and also could be a biomarker for synovial sarcoma [ 256 ].…”
Section: Micrornas In the Regulation Of Ribosomal Protein Coding Mmentioning
confidence: 99%